Theoretical calculation of CH3F/N2-broadening coefficients and their temperature dependence. (July 2018) - Jellali, C.; Maaroufi, N.; Aroui, H.
Highlights: N2 -broadening coefficients for transitions in the ν6 vibrational band of CH3 F have been calculated. The Robert and Bonamy semi-classical formalism with parabolic and exact trajectories was used. Temperature dependence exponents n for transitions in the ν6 band were computed for J up to 60 and K up to 10. Temperatures from 296 K down to 183 K have been considered. Abstract: Using Robert and Bonamy formalism (with parabolic and exact trajectories) based on the semi-classical impact theory, N2 -broadening coefficients of methyl fluoride CH3 F were calculated for transitions belonging to the P P-, P Q-, P R-, R P-, R Q- and R R- sub-branches of the ν6 perpendicular band near 8.5 µm. The calculations showed the predominance of the dipole–quadruple interaction. The J and K rotational quantum numbers dependencies of the computed coefficients that are consistent with previous measurements were clearly observed in this study. For a fixed value of J, we noticed a decrease in the broadening coefficients, which was more significant at lower J values. In order to deduce the temperature exponent, the N2 -broadening coefficients of CH3 F were calculated at various temperatures of atmospheric interest between 183 and 296 K with J ≤ 60 and K ≤ 10. These exponents were, in general, J-dependent and K-independent, except for K close to J.